Parameter Optimization of Traffic Cone Recycling Manipulator - Li Yushan; Liu yang; Lü Antao (Jixie chuandong)
Aiming at a single degree of freedom geared linkage traffic cone recovery manipulator,based on the kinematics analysis,the influence of parameters,likes link size and transmission ratio on the end actuator velocity and trajectory of recovery manipulator is researched. Considering reducing occupation space,main arm rotation angle and peak horizontal acceleration as the optimization targets,the mathematical model is established. By using MATLAB,the main arm rotation angle,main arm,deputy arm horizontal angle and gear transmission ratio are optimized. According to the design parameters before and after optimization,the dynamics simulation verification of the recycling manipulator is carried out by ADAMS. The result shows that,the optimization of the size of recovery manipulator is reduced by 10. 3%,main arm rotation angle decreased by 13. 6%,the peak horizontal acceleration is reduced by 19. 8%.